Investigating the role of IL-4/IL-13 signalling through the IL-4 receptor alpha (IL-4Rα) on keratinocytes in murine models of Leishmania major and Schistosoma mansoni - Govender, Melissa (Division of Immunology, 2017)
Keratinocytes represent the major cell type in the skin. During cutaneous leishmaniasis (CL) and schistosomiasis, the skin is important during the parasite life cycle. While Th1 immunity is required to control CL, protection during schistosomiasis requires Th2 immunity. Paradoxically, Th2 characteristic IL-4 secreted early during L. major infection in mice, can drive a Th1 response by instructing dendritic cells to produce IL-12. Additionally, keratinocytes at the site of L. major infection in C57BL/6 mice, were postulated to be the source of the IL-4. We investigated if IL-4/IL-13 signalling via the IL-4Rα on keratinocytes contributed to early immunity during CL and schistosomiasis. Keratinocyte-specific IL-4Rα deficient (KRT14creIL-4Rα-/lox) BALB/c and C57BL/6 mice were generated by gene targeting and site-specific recombination (cre/loxP) under control of the KRT14 locus. In the L. major footpad model, KRT14creIL-4Rα-/lox BALB/c mice developed increased swelling, high parasite burdens, and cytokine and antibody secretion similar to littermate controls. L. major-infected KRT14creIL-4Rα-/lox C57BL/6 mice had decreased footpad swelling, low parasite burdens, a dominant Th1 cytokine response, and low type 1 and 2 antibody titres, similar to littermate control and resistant C57BL/6. In the L major ear model, KRT14creIL-4Rα-/lox BALB/c mice developed increased swelling, high parasite burdens, Th1 and Th2 cytokines, and high antibody titres, similar to littermate controls. L. major LV39-infected KRT14creIL-4Rα-/lox BALB/c mice showed significantly decreased parasite burdens in the ear, compared to littermate controls. L. major-infected KRT14creIL-4Rα-/lox C57BL/6 mice in the ear model, had decreased swelling, low parasite burdens, a dominant Th1 immune response, and low type 1 and 2 antibody titres, similar to littermate control and C57BL/6 mice. In the Schistosoma model, survival of S. mansoni-infected KRT14creIL-4Rα-/lox BALB/c mice was similar to littermate controls during mortality studies. During acute infection, S. mansoni-infected KRT14creIL-4Rα-/lox BALB/c mice showed gut pathology, hepatosplenomegaly, cytokine production, low type 1 and high type 2 antibodies, similar to littermate controls. In comparison to littermate controls, S. mansoni-infected KRT14creIL-4Rα-/lox BALB/c mice had smaller granulomas. Collectively, our results indicate that IL-4/IL-13 signalling through the IL-4Rα on keratinocytes is not required for control during CL or acute schistosomiasis, but does contribute to efficient granuloma formation during acute schistosomiasis.